System-level seismic resilience assessment of reinforced masonry shear wall buildings with masonry boundary elements. (August 2020) - Hosseinzadeh, Shadman; Galal, Khaled
Abstract: The concept of seismic resilience plays an important role in seismic assessment of structures as it assesses the capability of a system to withstand an unwanted event, such as earthquakes, by estimating the losses and determining the system's functionality and sustainability during and after such event. In this study, a framework was utilized to assess the seismic resilience of Reinforced Masonry Shear Wall (RMSW) buildings as well as studying the impact of incorporating Masonry Boundary Elements (MBEs) at the ends of RMSW. To achieve this goal, a ten-story RMSW building was numerically modelled in OpenSees to assess the seismic performance and resilience of the system when adding confined MBEs. The selected building is located in Montreal, Canada, and initially designed to be built having rectangular walls. Subsequently, the walls were redesigned to integrate MBEs at their outermost fibre to help increase the ductility and strength of the RMSWs. A full 3D wide-column macro-modelling approach was used to simulate the dynamic response of the archetype building. Validation of the modelling approach was done against available experimental tests as an initial step to ensure the robustness of the model in predicting the inelastic response of the building. Subsequently, the models were analyzed against multiple ground motion records using Incremental Dynamic Analysis to identify the initiation of collapse alongside developing the fragility curves of the building. The system-level seismic performance of the building was assessed after incorporating MBEs. The resilience of the building was assessed using the developed fragility functions, and a comparison was made to highlight the effect of using MBEs on the response of the studied RMSW building. The results showed a significant enhancement in the seismic resilience of the building by using confined MBEs at the shear walls' extreme.